2017
DOI: 10.1098/rspb.2017.1427
|View full text |Cite
|
Sign up to set email alerts
|

Extreme diel dissolved oxygen and carbon cycles in shallow vegetated lakes

Abstract: A common perception in limnology is that shallow lakes are homogeneously mixed owing to their small water volume. However, this perception is largely gained by downscaling knowledge from large lakes to their smaller counterparts. Here we show that shallow vegetated lakes (less than 0.6 m), in fact, undergo recurring daytime stratification and nocturnal mixing accompanied by extreme chemical variations during summer. Dense submerged vegetation effectively attenuates light and turbulence generating separation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 46 publications
2
76
1
Order By: Relevance
“…of the water column) contrasts with findings of Vilas et al (2017), who found oxygen effects at 50% P. crispus cover in a shallow Australian lake following temperature stratification (not observed in the unstratified hydropeaking reservoir, but see also Andersen et al, 2017;Ribaudo et al, 2018;Torma & Wu, 2019). The main mechanisms involved in these small-scale differences likely involve and ferrous iron from bottom sediments (Andersen et al, 2017;James, Dechamps, Turyk, & McGinley, 2007;Ribaudo et al, 2018).…”
Section: Spatial Scales Of Invasive Macrophyte Effectsmentioning
confidence: 65%
“…of the water column) contrasts with findings of Vilas et al (2017), who found oxygen effects at 50% P. crispus cover in a shallow Australian lake following temperature stratification (not observed in the unstratified hydropeaking reservoir, but see also Andersen et al, 2017;Ribaudo et al, 2018;Torma & Wu, 2019). The main mechanisms involved in these small-scale differences likely involve and ferrous iron from bottom sediments (Andersen et al, 2017;James, Dechamps, Turyk, & McGinley, 2007;Ribaudo et al, 2018).…”
Section: Spatial Scales Of Invasive Macrophyte Effectsmentioning
confidence: 65%
“…ponds isolated from other waterways, large dead zones stretching hundreds of kilometres) (Diaz, 2001;Diaz and Rosenberg, 2008). Animals can also be exposed to intermittent cycles of hypoxia, in which bouts of low O 2 are separated by periods of normoxia (or even hyperoxia), as is common in tide pools, estuaries, coral reefs and heavily vegetated systems (Andersen et al, 2017;Breitburg, 1992;Diaz, 2001;Nilsson and Renshaw, 2004;Richards, 2011;Tyler et al, 2009). Instances of both constant hypoxia and intermittent hypoxia are well documented in aquatic environments, but the biological effects of the latter have received comparably little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwaters are important components of regional and global carbon budgets (Duarte and Prairie, 2005;Raymond et al, 2013). Lakes in particular have received attention as hotspots of carbon cycling emitting CO 2 and CH 4 to the atmosphere (Tranvik et al, 2009;Holgerson and Raymond, 2016;Bastviken et al, 2011;Wik et al, 2016). However, the role and magnitude of carbon emissions from lakes remain uncertain as the estimated gas fluxes often depend on empirical models of gas exchange velocity with substantial uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of convection on gas exchange velocity and the resulting gas flux may thus be missed if not accounted for (Holgerson et al, 2016;Podgrajsek et al, 2015). Small lakes (< 0.01 km 2 ) are globally abundant and may comprise up to 20 % of the total surface area of lakes (Holgerson and Raymond, 2016) and extensive changes in CO 2 concentrations and vertical mixing make single or even several daytime measurements of CO 2 fluxes insufficient to calculate daily fluxes (Holgerson et al, 2016;Andersen et al, 2017). Increasing the temporal resolution and measuring gas flux during day and night time would enable better models of gas exchange velocity and large-scale carbon budgets.…”
Section: Introductionmentioning
confidence: 99%